Tinjauan Pustaka Keterkaitan antara GCG, CSR dan Sustainability Bisnis Digital - Kuswara, Zakaria; Soeratin, Harry Z. (GLOBAL SCIENTS PUBLISHER, 2025)
This research explores the relationship between (GCG) and (CSR) in supporting business sustainability in the digital era. GCG acts as a framework to ensure company management is carried out in a transparent and accountable manner, while CSR focuses on positive contributions to society and the environment. Collaboration between the two not only strengthens the company's reputation, but also strengthens relationships with stakeholders, contributing to long-term sustainability. Implementing GCG and CSR simultaneously can improve financial performance through operational efficiency, increasing investor attractiveness and customer loyalty. In the digital era, technology provides tools to measure and report social and environmental impacts with more precision, while facilitating active stakeholder participation. By utilizing technological innovation, companies can increase transparency and effectiveness in implementing sustainability practices. This research is expected to make an important contribution to the development of management theory and practice and offer recommendations for more sustainable business practices in the future.